2022
DOI: 10.3390/jcm11030771
|View full text |Cite
|
Sign up to set email alerts
|

Pain Burden in Post-COVID-19 Syndrome following Mild COVID-19 Infection

Abstract: The global pandemic of SARS-CoV-2 has affected several hundred million people, and many infected people have suffered from a milder initial infection but have never fully recovered. This observational study investigates the pain burden in sufferers of post-COVID-19 syndrome after a milder initial infection. One hundred post-COVID-19 patients filled out questionnaires regarding sociodemographic data, previous comorbidities, present pharmacological treatment, pain intensity and pain localisation. Health-related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
46
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(52 citation statements)
references
References 32 publications
3
46
0
Order By: Relevance
“…Only 6 of the 35 studies reported risk factors associated with the prevalence of MSK symptoms in Long COVID patients. 27 , 30 , 31 , 38–40 Sex differences were found in 3 studies, with females being significantly more likely to report myalgia ( p = 0.022 in Iqbal et al); 41 p < 0.01 in Taquet et al, 40 and arthralgia (p < 0.05 in Sykes et al) 42 than males. Two studies reported opposite trends for the association between age and prevalence of MSK pain of different origin, with increasing age associated with increased prevalence of arthralgia (p < 0.001 in Iqbal et al), 41 and decreased prevalence of myalgia (p < 0.05 in Taquet et al).…”
Section: Synthesis Of Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…Only 6 of the 35 studies reported risk factors associated with the prevalence of MSK symptoms in Long COVID patients. 27 , 30 , 31 , 38–40 Sex differences were found in 3 studies, with females being significantly more likely to report myalgia ( p = 0.022 in Iqbal et al); 41 p < 0.01 in Taquet et al, 40 and arthralgia (p < 0.05 in Sykes et al) 42 than males. Two studies reported opposite trends for the association between age and prevalence of MSK pain of different origin, with increasing age associated with increased prevalence of arthralgia (p < 0.001 in Iqbal et al), 41 and decreased prevalence of myalgia (p < 0.05 in Taquet et al).…”
Section: Synthesis Of Resultsmentioning
confidence: 92%
“… Not available Bellan et al (2021) 89 Italy 200 (122/78) Yes Prospective longitudinal study Baseline, 17 weeks and 52 weeks. Arthralgia/myalgia Baseline (19.3%) At week 17 (6.5%) At week 52 (21.9%) Not available Not available Not available Bileviciute-ljungar et al (2022) 31 Sweden 100 (18/82) No (90%) Yes (10%) Cross-sectional study A mean of 47 weeks since the start of the infection. Head/face 27% Throat/neck 5% Shoulder/arms 5% Chest 16% Legs 12% Pain sites varied 15% The mean value of pain intensity during the last week was 4.4/10 75% reported generalized pain.…”
Section: Synthesis Of Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This prevalence rate was based on studies investigating general post-COVID symptomatology. In fact, the prevalence of musculoskeletal post-COVID pain raised to rates ranging from 45% to 60% in studies focusing on or specifically investigating this symptom [ 5 , 6 , 7 , 8 , 9 ]. Further, Yelin et al have defined the so-called “pain-syndrome pattern”, a subgroup of subjects with pain as the main post-COVID symptom [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…To date, it seems that post-COVID pain has a musculoskeletal origin [ 4 ]; however, a neuropathic pain origin is also plausible [ 5 ]. An increasing number of studies reported the presence of musculoskeletal post-COVID pain in up to 60% of the COVID-19 survivors [ 6 , 7 , 8 , 9 ]. The number of studies investigating the prevalence of neuropathic post-COVID pain is lower in relation to those assessing musculoskeletal post-COVID pain [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%